Krajevni govori ob Čabranki in zgornji Kolpi - Gostenčnik, Januška (Linguistica et philologica, 2018)
The monograph presents local dialects in Slovenia and Croatia. The local dialects researched which lie in the south of Slovenia are classified into northern part of Kostel dialect, which is a part of Lower Carniolan dialect group of Slovene language, according to traditional Slovene dialectology. Demarcation between Slovene (and Croatian) language and their dialects using political border between Slovenia and Croatia in this area is a reflection of solely sociolinguistic, not an all-encompassing linguistic thought, which would take into account developmental linguistic characteristics of these local dialects and demarcate between them on the basis of historical linguistic development. A hypothesis was to be proven, using defining characteristics of Slovene language system, that some of the local dialects, currently classified into West Goran subdialect of Goran dialect of Croatian language are, from linguogenetic perspective, a part of the same language system as the north part of Kostel dialect (according to old nomenclature) or Čabranka dialect (according to new nomenclature) - i.e., these local dialects are a part of Slovene language system and not Croatian Kajkavian regiolect. Sociolinguistic aspects of language or nationality were a subject neither of interest nor of research.